The Effect of Fish Oil, Vitamin D and Protein on URTI Incidence in Young Active People - Da Boit, M.; Gabriel, B. M.; Gray, P.; Gray, S. R. (International Journal of Sports Medicine, 2015)
Upper respiratory tract infections (URTI) are a frequent illness among athletes. We investigated the effect of a multi-nutrient supplement (vitamin D, fish oil and protein) on the occurrence of URTI in young active people. 42 young recreational athletes were randomly assigned to receive either supplementation (550 mg DHA, 550 mg EPA, 10 µg vitamin D3 and 8 g whey protein) or placebo for 16 weeks. Unstimulated saliva samples were collected by passive drool. Samples were analysed for IgA (sIgA) concentration and the secretion rate extrapolated by multiplying concentration by saliva flow rate. Physical activity levels and URTI incidence were monitored by questionnaire. Training status was not different between the 2 groups. There were no differences in the incidence, severity and duration of URTI. However the number of symptom days was lower in the supplemented compared to the control group (1.72±1.67 vs. 2.79±1.76; P<0.05). sIgA concentration and secretion rate did not differ between groups. This study demonstrates that 16 weeks of supplementation with fish oil, vitamin D and protein did not modify the incidence, severity and duration of URTI, although the total number of symptom days was reduced, in a healthy active population.
Keywords: immune; exercise; nutrition